Análise de transcritoma e expressão gênica de feijoeiro comum (Phaseolus vulgaris L.) submetido ao estresse abiótico - Pereira, Wendell Jacinto (2016)
The common bean (Phaseolus vulgaris L.) is an important foodstuff strongly associated with an issue if global food security. Among the factors that affect their agricultural production, abiotic stress episodes listed as high risk and impact, can restrict the area under cultivation and crop yields. The characterization of high-throughput differential gene expression involved in plant response to abiotic stresses enables profile the genes, and the metabolic pathways, involved in the mechanisms of tolerance to abiotic stresses. In this study, the expression of genes related to response to drought stress in leaf and root tissue of two contrasting common bean genotypes for stress tolerance was evaluated by RNA-Seq. A new Phaseolus vulgaris transcriptome was built featuring 1,668 new loci and 23,169 new isoforms. In all, 54,807 transcripts were identified, found being distributed in 28,640 genes. Through the edgeR package (Bioconductor), they determined by differential expression analysis of leaf and root 1,242 differentially expressed genes. Of these, 458 genes had different expression in tolerant genotype (191 up-regulates and 267 down-regulated) when compared to the sensitive genotype. Functional annotation revealed in tolerant genotype predominance of genes in the categories enriched oxidoreductase activity, oxidation-reduction process, regulation of gene expression, regulation of macromolecule metabolic process and dioxygenase activity. By qPCR, of the 15 DEGs identified via RNA-Seq and selected for characterization, 74.42% were validated for differential expression. Additionally, a total of 151,283 variants were identified, of which 135,167 are SNPs and 16,115 are indels. Through functional annotation, performed in SnpEff v.4.2, were identified 330,378 effects caused by variants. The data used in this study were deposited in the Sequence Read Archive (NCBI) and will be available. The results of this study contribute to the expansion of knowledge about the gene mechanisms, as well as their functional variants, related to abiotic stresses tolerance in beans.